Neo Al-Ma'un Theology and Social Improvement of Society - Harya Putra, Haritza Bayu; Arifin, Syamsul (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2024)
It is necessary to study the theological theme of Al-Ma'un because of its developmentMustadh'afin are not only those who are orphans but those who are oppressed socially, structurally and culturally. The article aims to provide further explanation regarding Al-Maun theology and social improvement. This research uses qualitative methods with a library approach. After all data sources have been collected, the author conducts a literature review and reviews existing literacy sources. Results of this research: 1) In Al-Qusyairi's work, Al-Ma'uun's letter is named Ad-Diin. This may be taken as the last word at the end of the first verse of the surah, as is done with the name of surah An-Naas in the last surah in the Urdu mushaf. 2) KH. Ahmad Dahlan taught Surah al-Ma'un from the Qur'an to his students several times over a relatively long period of time. The point of this letter is that ritual worship has no meaning unless the perpetrator performs social charity. This surah even calls those who ignore orphans and do not try to eradicate poverty in society as "religious liars. In surah al-Ma'un, it is stated that as Muslims who have the ability to help orphans and the poor, we must help each other and share a little of what we have to help them overcome their difficulties.